Does inundation risk affect leaf-cutting ant distribution? A study along a topographic gradient of a Costa Rican tropical wet forest - Silva, Paulo S. D. (2014)
Successional state of forest and availability of pioneer plants are recognized factors affecting densities of leaf-cutting ants. However little is known about how abiotic factors can shape nest distributions. We investigated the effect of topography, soil, forest successional state and inundation risk on nest density and size of Atta cephalotes colonies along streams in a tropical wet forest in Costa Rica. In each forest type, we surveyed 12 sites, each site comprising five transects (10 × 100 m) varying in topography and proximity to streambeds. We found no difference regarding nest size or density between forest types or soil consociation. Nest density varied with topographic environment, with significantly higher nest density on slope tops (farther from streambeds) and without colonies in valley bottoms (closer to streambeds). Nests found in areas affected by the last great inundation before our study were scarcer and smaller than nests in non-flooded areas. We showed that inundation events favour an accumulation of Atta colonies towards higher sites, where they are also allowed to become larger and may survive longer. Inundation risk may be a strong force shaping the distribution of leaf-cutting ant nests in tropical floodplain forests, even concealing the relevance of successional state of forest.